Engineered Bacterial Cellulose Nanostructured Matrix for Incubation and Release of Drug-Loaded Oil in Water Nanoemulsion - Di Natale, Concetta; De Gregorio, Vincenza; Lagreca, Elena; Mauro, Francesca; Corrado, Brunella; Vecchione, Raffaele; Netti, Paolo Antonio (Frontiers in Bioengineering and Biotechnology, 2022)
Bacterial cellulose (BC) is a highly pure form of cellulose produced by bacteria which possesses numerous advantages such as good mechanical properties, high chemical flexibility, and the ability to assemble in nanostructures. Thanks to these features, it achieved a key role in the biomedical field and in drug delivery applications. BC showed to be able to modulate the release of several drugs and biomolecules to the skin, thus, improving their clinical outcomes. This work displays the loading of a 3D BC nanonetwork with an innovative drug delivery nanoemulsion system. The BC was optimized by static culture of SCOBY (symbiotic colony of bacteria and yeast) and characterized by morphological and ultrastructural analyses, which indicate a cellulose fiber diameter range of 30-50 nm. BC layers were then incubated at different time points with a nanocarrier based on a secondary nanoemulsion (SNE) previously loaded with a well-known antioxidant and anti-inflammatory agent, namely Coenzyme-Q10 (Co-Q10). Incubation of Co-Q10 – SNE in the BC nanonetwork and its release were analyzed by fluorescence spectroscopy.